The Organically Cultivation Techniques of Curly Chili in Handayani Farming Group, Sidokaton Village, Gisting District - Kartina, Raida; Prajaka, Nanang Wahyu; Darma, Wika Anrya; Putri, Sekar Utami; Jumawati, Riana (Universitas Sahid Surakarta, 2024)
Abstract: This community service aims to guide chili farmer groups, especially the Handayani farmer group, to start cultivating chili plants organically on their farming land.There were three stages of the implementation method used, namely increasing knowledge, increasing skills and evaluation. Increasing knowledge was given through lectures to provide knowledge about the cultivation of organic chili plants, botanical pesticides and production of compost made from Azolla pinnata; followed by skills improvement by making botanical pesticides, propagating Azolla pinnata and making compost, demonstration plots of chili plants and then evaluation. Guidance for demonstrations on how to cultivate organic chilies started with planting seeds on the ridge, applying azolla compost to the planting holes, then planting chilies and applying botanical pesticides. Farmers planted chilies in beds that had been made as many as 192 plants which were divided into 6 beds. Afterwards, there were carried out the maintenance activities, controlling pests and diseases with the application of botanical pesticides, and harvesting along with post-harvest handling. This activity would be monitored. Monitoring was carried out once a month, especially at the end of each group of practiced cultivation activities. As an indicator of success, the results of the activity evaluation showed an increase in knowledge of organic farming concepts of 55% and an increase in skills of 85%. Keywords: Sidokaton village, Pesticide Organic, Azolla pinnata